ANALISIS MOTIVASI INTRINSIK MAHASISWA AKUNTANSI UNIVERSITAS SURABAYA TERHADAP PENGAMBILAN PUTUSAN BERKARIER DI KANTOR AKUNTAN PUBLIK BIG FOUR ATAU NON-BIG FOUR - Kevin Kurniawan; Wiyono Pontjoharyo (CALYPTRA, 2018)
The research conducted to discuss about intrinsic motivation analysis for Universitas Surabaya’s students in career decision making in Big Four or non-Big Four public accounting firm. This research aims to unlock the mystery of whether the drive (the intrinsic motivation theory) can be applied or notto the decision making of student career in Big Four or non-Big Four public accounting firm. This research is expected to give benefit to the students as the main subject especially the accounting majors to have an insight about career decision in Big Four or non-Big Four public accountant firm. Research data, participant observation, and interview results that have been processed in a structured design, have produced a key to answer the mystery in this research. Using data from a viewpoint of the Big Four or non-Big Four public accounting firm’ personnel, carries an outcome where the drive cannot be entirely applicable in career decision making but drive can be the basis for a person to establish himself in career decision making. In addition, the drive that becomes a shield can control a person to keep on track in a career decision that suits him/her.